Adipokine zinc‐α2‐glycoprotein regulated by growth hormone and linked to insulin sensitivity. (7th August 2014) - Balaz, Miroslav; Ukropcova, Barbara; Kurdiova, Timea; Gajdosechova, Lucia; Vlcek, Miroslav; Janakova, Zuzana; Fedeles, Jozef; Pura, Mikulas; Gasperikova, Daniela; Smith, Steven R.; Tkacova, Ruzena; Klimes, Iwar; et al.
<x xml:space="preserve">Abstract</x> Objective Hypertrophic obesity is associated with impaired insulin sensitivity and lipid‐mobilizing activity of zinc‐α2‐glycoprotein. Adipose tissue (AT) of growth hormone (GH) ‐deficient patients is characterized by extreme adipocyte hypertrophy due to defects in AT lipid metabolism. It was hypothesized that zinc‐α2‐glycoprotein is regulated by GH and mediates some of its beneficial effects in AT. Methods AT from patients with GH deficiency and individuals with obesity‐related GH deficit was obtained before and after 5‐year and 24‐month GH supplementation therapy. GH action was tested in primary human adipocytes. Relationships of GH and zinc‐α2‐glycoprotein with adipocyte size and insulin sensitivity were evaluated in nondiabetic patients with noncancerous cachexia and hypertrophic obesity. Results AT in GH‐deficient adults displayed a substantial reduction of zinc‐α2‐glycoprotein. GH therapy normalized AT zinc‐α2‐glycoprotein. Obesity‐related relative GH deficit was associated with almost 80% reduction of zinc‐α2‐glycoprotein mRNA in AT. GH increased zinc‐α2‐glycoprotein mRNA in both AT of obese men and primary human adipocytes. Interdependence of GH and zinc‐α2‐glycoprotein in regulating AT morphology and metabolic phenotype was evident from their relationship with adipocyte size and AT‐specific and whole‐body insulin sensitivity. Conclusions The results demonstrate that GH is involved in regulation of AT zinc‐α2‐glycoprotein; however, the molecular mechanism linking GH and zinc‐α2‐glycoprotein in AT is yet unknown.